French & Indian Wars in Maine - Dekker, Michael (Charleston, SC : The History Press, 2015)
"Between 1675 and 1749, British, French and Native Americans clashed in six distinct wars to stake and defend their land claims. These dark, tragic and largely forgotten struggles laid the foundation of Maine"--P. [4] of cover.
Includes bibliographical references and index.
Maine author.
Keywords: Indians of North America -- Wars -- 1600-1750.; United States -- History, Military -- To 1900.; Maine -- History -- French and Indian War, 1754-1763.; Maine -- History -- 17th century; Maine -- History -- 18th century; United States -- History -- King William's War, 1689-1697.; Maine -- History -- King William's War, 1689-1697.; United States -- History -- Queen Anne's War, 1702-1713.; Maine -- History -- Queen Anne's War, 1702-1713.; United States -- History -- King George's War, 1744-1748.; Maine -- History -- King George's War, 1744-1748.; United States -- History -- French and Indian War, 1754-1763.; Maine -- History -- French and Indian War, 1754-1763.; Great Britain -- Military relations -- France; France -- Military relations -- Great Britain